Comparative Analysis of Physical and Chemical Quality Parameters of Turmeric Varieties Subjected to Different Blanching Methods - Bijay Lamsal; Pratistha Adhikari; Shree Neupane; Rijwan Sai; Himanchal Adhikari; Sanjay Kandel; Aayush Pokhrel (Turkish Journal of Agriculture: Food Science and Technology)
Turmeric (Curcuma longa Linn.) is widely recognized for its medicinal properties; however, the potential of Nepalese turmeric varieties, specifically Kapurkot Haledo 1 (KK1), Kapurkot Haledo-2 (KK2), and Sugandha, remains underexplored, particularly in relation to their processing outcomes and quality characteristics. This study aimed to evaluate the effects of different blanching methods on these varieties' quality traits. Using a Completely Randomized Design (CRD), the experiment tested three blanching treatments: distilled water boiling (DWB), alkaline water boiling (AWB), and a control, with nine treatment combinations, each replicated four times. Statistical analysis showed that KK2 had the highest dry recovery percentage (23.51%), with DWB proving more effective than AWB. KK1 exhibited the most significant length shrinkage, whereas KK2 treated with AWB showed the least. In terms of diameter, KK1 and Sugandha showed the highest shrinkage, while KK2 treated with AWB demonstrated minimal shrinkage. For color quality, KK1 received the highest color score (6.75), followed by Sugandha and KK2, with AWB generally enhancing color ratings across the varieties. Significant interactions between turmeric variety and blanching method were observed. Specifically, KK1 with DWB achieved the highest dry recovery, similar to KK2 under AWB treatment. Additionally, Sugandha treated with AWB showed the least length shrinkage, and KK2 exhibited the lowest diameter shrinkage under both control and AWB treatments. Regarding oil content, KK1 and Sugandha retained the highest levels under control conditions, while KK2 with AWB showed the lowest ash content and the highest curcumin concentration in the control group. In summary, the findings suggest that the combination of KK2 with AWB or DWB yields optimal outcomes across multiple quality parameters, underscoring the effectiveness of these blanching methods as post-harvest processing techniques for enhancing the quality of Nepalese turmeric.